2014
DOI: 10.1007/s00216-014-8086-z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction and field-amplified sample injection–capillary zone electrophoresis for the analysis of benzophenone UV filters in environmental water samples

Abstract: 27A field amplified sample injection-capillary zone electrophoresis (FASI-CZE) 28 method for the analysis of benzophenone (BP) UV-filters in environmental water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Table summarizes other methods developed for analysis of various kinds of food and water. In many of these applications, some kind of offline sample treatment was used additionally to the stacking technique, viz., SPE , dispersive SPE , SPE by a molecularly imprinted polymer , LLE , and accelerated solvent extraction .…”
Section: Concentration Adjustment (Kohlrausch Stacking)mentioning
confidence: 99%
“…Table summarizes other methods developed for analysis of various kinds of food and water. In many of these applications, some kind of offline sample treatment was used additionally to the stacking technique, viz., SPE , dispersive SPE , SPE by a molecularly imprinted polymer , LLE , and accelerated solvent extraction .…”
Section: Concentration Adjustment (Kohlrausch Stacking)mentioning
confidence: 99%
“…Tris-H 3 PO 4 was used as BGE system, and the effects of ionic strength (20,30,50, 70 mmol/L Tris solution), pH (2.2, 2.7, 3.2, 3.7) and organic additive (CH 3 OH) on the CE separation of target analytes were carefully investigated, respectively. The results showed that the ionic strength had a negligible effect on resolution, and 70 mmol/L of Tris providing the highest conductivity was chosen for subsequent experiment.…”
Section: Optimization Of Ce Separation Conditionsmentioning
confidence: 99%
“…In addition, electrokinetic injection is used instead of hydrodynamic injection for better preconcentration potential through sample stacking. FASI is the most simple and effective concentration technique that commonly used for stacking inorganic ions or ionic organic compounds, and has been widely used for concentrating organic pollutants , receptor antagonist , and drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the use of capillary electrophoresis (CE) techniques has increased as an alternative to LC because of its high efficiency, rapid analysis, and low reagent consumption, and several applications dealing with the analysis of BPs in environmental [20,21] and cosmetic [22][23][24][25][26][27][28] samples can be found in the literature. Among CE techniques, micellar electrokinetic chromatography (MEKC), a CE mode that allows the separation of hydrophobic analytes by the combination of electrophoretic and chromatographic effects, and the only CE mode able to separate both neutral and charged analytes, has also been employed for the analysis of BPs although mainly in cosmetic matrices [22,24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Once the analytes enter the capillary they stack up in the boundary region between the high-resistivity solvent and the background electrolyte (BGE) and separation will take place. An off-line SPE-FASI-CZE method was recently developed for the analysis of eight BPs in river water samples [21].…”
Section: Introductionmentioning
confidence: 99%